Resilient solar photovoltaic supply chain network design under business-as-usual and hazard uncertainties. (4th March 2018) - Dehghani, Ehsan; Jabalameli, Mohammad Saeed; Jabbarzadeh, Armin; Pishvaee, Mir Saman
Highlights: An optimization model to design a solar photovoltaic supply chain is proposed. The model is able to consider business-as-usual and hazard uncertainties. To cope with business-as-usual uncertainty, a robust optimization approach is developed. Several resilience strategies are applied to improve the resilience level of the supply chain. The capabilities of the model are demonstrated through conducting a real case study. Abstract: Unlike their inherent advantageous features, photovoltaic systems have not yet penetrated the market adequately due to their high price against other electricity generation options. To propel this fledgling industry further towards commercialization, the efficient and effective design of its supply chain is of paramount importance. In this regard, this study proposes a hybrid robust-scenario based optimization model to design a resilient photovoltaic supply chain under both business-as-usual and hazard uncertainties. To capture business-as-usual uncertainty, a customized robust optimization method is developed, which is capable of tackling correlated uncertain parameters and adjusting the level of conservatism in the solutions. Likewise, a number of proactive and reactive resilience strategies are incorporated into the model to ameliorate the resilience level of the concerned supply chain in the presence of hazard uncertainty. The capabilities of the developed model are explored by discussing a real case study via which helpful managerial insights are gained.